Tertiary lymphoid structures accompanied by fibrillary matrix morphology impact anti-tumor immunity in basal cell carcinomas - Byers, Candice; Gill, Melissa; Kurtansky, Nicholas R.; Alessi-Fox, Christi; Harman, Maggie; Cordova, Miguel; Gonzalez, Salvador; Guitera, Pascale; Rotemberg, Veronica; Marghoob, Ashfaq; Chen, Chih-Shan Jason; Dy, Jennifer; et al. (Frontiers in Medicine, 2022)
Tertiary lymphoid structures (TLS) are specialized lymphoid formations that serve as local repertoire of T- and B-cells at sites of chronic inflammation, autoimmunity, and cancer. While presence of TLS has been associated with improved overall outcomes in many cancers as well as predictive of response to immune checkpoint blockage therapies in several solid tumors, its prognostic value in basal cell carcinoma (BCC) has not been investigated. Herein, we determined the prognostic impact of TLS using tumor infiltrating lymphocytes (TILs) and tumor killing as outcome measures of anti-tumor immunity to relate with TLS prevalence and maturation. In 30 distinct BCCs, we show the presence of TLS was significantly enriched in tumors harboring a nodular component and more mature primary TLS was associated with determinants of anti-tumor immunity. Moreover, assessment of the fibrillary matrix surrounding tumors showed discrete morphologies were significantly associated with higher TIL counts, critically accounting for heterogeneity in TIL count distribution within TLS maturation stages. Specifically, increased length of fibers and lacunarity of the matrix with concomitant reduction in density and alignment of fibers were present in tumors displaying high TIL counts. Given the interest in inducing TLS formation as a therapeutic intervention as well as its documented prognostic value, elucidating potential impediments to the ability of TLS in driving anti-tumor within the tumor microenvironment warrants further investigation. These results begin to address and highlight the need to integrate stromal features which may present a hindrance to TLS formation and/or effective function as a mediator of immunotherapy response.